The desperate hours : one hospital's fight to save a city on the pandemic's front lines - Brenner, Marie (Flatiron Books, 2022)
"A remarkable depiction of a city in crisis - based on new, behind-the-scenes reporting - that captures the resilience, peril, and compassion of the early days of the Covid pandemic In the spring of 2020, COVID-19 arrived in New York City. Before long, America's largest metropolis was at war against a virus that mercilessly swept through its five boroughs. It became apparent that if Covid wasn't somehow halted, the death count in New York alone would be in the hundreds of thousands. And if New York's hospitals failed, what chance did the rest of the country have? In The Desperate Hours, award-winning journalist Marie Brenner, having been granted unprecedented 18-month access to the entire New York-Presbyterian hospital system, tells the story of the doctors, nurses, residents, researchers, and suppliers who tried to save lives across Manhattan, Queens, and Brooklyn and the northern periphery of the city. Drawing on more than 200 interviews, Brenner takes us inside secure ICU units, sealed operating rooms, locked executive suites, unknown basement workshops, and makeshift clinics to provide extraordinary witness to the war as it was waged on the front line. But The Desperate Hours is more than a thrilling account of medicine under extreme pressure. It is an intimate portrait of courageous men and women coming together in their devotion to duty, their families, each other, and the city they loved more than any other"--